Diagnostic Errors in the Pediatric and Neonatal ICU. Issue 1 (January 2015) - Custer, Jason W.; Winters, Bradford D.; Goode, Victoria; Robinson, Karen A.; Yang, Ting; Pronovost, Peter J.; Newman-Toker, David E.
<x xml:space="preserve">Abstract</x> Objective: Diagnostic errors lead to preventable hospital morbidity and mortality. ICU patients may be at particularly high risk for misdiagnosis. Little is known about misdiagnosis in pediatrics, including PICU and neonatal ICU. We sought to assess diagnostic errors in PICU and neonatal ICU settings by systematic review. Data Sources: We searched PubMed, Embase, CINAHL, and Cochrane. Study Selection: We identified observational studies reporting autopsy-confirmed diagnostic errors in PICU or neonatal ICU using standard Goldman criteria. Data Extraction: We abstracted patient characteristics, diagnostic error description, rates and error classes using standard Goldman criteria for autopsy misdiagnoses and calculated descriptive statistics. Data Synthesis: We screened 329 citations, examined 79 full-text articles, and included 13 studies (seven PICU; six neonatal ICU). The PICU studies examined a total of 1, 063 deaths and 498 autopsies. Neonatal ICU studies examined a total of 2, 124 neonatal deaths and 1, 259 autopsies. Major diagnostic errors were found in 19.6% of autopsied PICU and neonatal ICU deaths (class I, 4.5%; class II, 15.1%). Class I (potentially lethal) misdiagnoses in the PICU (43% infections, 37% vascular) and neonatal ICU (62% infections, 21% congenital/metabolic) differed slightly. Although missed infections were most common in both settings, missed vascular events were more common in the PICU and missed congenital conditions in the neonatal ICU. Conclusion: Diagnostic errors in PICU/neonatal ICU populations are most commonly due to infection. Further research is needed to better quantify pediatric intensive care–related misdiagnosis and to define potential strategies to reduce their frequency or mitigate misdiagnosis-related harm.